Application Smart Internship System Unika Soegijapranata (SISTA) berbasis Web (Progressive Web Apps) - Ilham Riski Wibowo; Ridwan Sanjaya; Hendra Prasetya (Soegijapranata Catholic University, 2022)
Apprenticeship is a student activity carried out on the basis of cooperation between the University and the institution where the work apprenticeship program is implemented which aims to be a place of learning as well as training for students to assess students' knowledge and understanding of the learning that has been given on campus and applied directly to the world of work at once Where there are difficulties in getting information on job apprenticeship vacancies, students usually search by contacting related agencies or seeing job internship vacancies on the online platform of each agency, which if accommodated will be very time consuming.Therefore a media is needed to accommodate information on vacancies as well as a place to register for an internship program that is easy, fast and easy to use by students and companies to create job apprenticeship vacancies.Purpose of this research is to make an application that can accommodate all of these activities from opening and looking for job apprenticeship program vacancies, approving and collaborating on apprenticeship programs as well as providing value or results of an integrated internship program with transcript information and Certificate of Companion Diploma (SKPI) Students. This media will be designed using a web application as well as the use of a progressive web app to be used on all types of platforms.